THE EFFECT OF HEALTH EDUCATION USING ANIMATION VIDEO MEDIA ON KNOWLEDGE ABOUT SEXUAL VIOLENCE ON CHILDREN IN STATE ELEMENTARY SCHOOL 05 BENGKULU CITY - Yuniarti Yuniarti; Devi Sulihayati; Susilo Damarini; Wewet Savitri (Proceeding B-ICON, 2022)
According to data from the Ministry of Women's Empowerment and Child Protection (Kemen PPPA) in 2020 the percentage of victims of violence against children by type of sexual violence was recorded (46.70%). This study aims to determine the effect of health education using animated videos on knowledge about sexual violence in children state elementary school 05 in Bengkulu City.The design of this study is a quasi-experimental method with the aim of explaining and clarifying the occurrence of a relationship. Control Group design with a pretest posttest group design approach, namely research by giving a pretest, then giving health education to a group after that a posttest is carried out. The results showed that among 42 children there was a difference in the average score of knowledge before and after being given health education using animated videos in the intervention group and leaflet media in the control group. Based on the results of the bivariate analysis using the Wilcoxon test, the value of p = 0.000 (p-value <0.05), means that there is a significant effect between health education in the intervention group on children's knowledge about sexual violence. Suggestions for schools to routinely conduct health education about sexual violence delivered through animated video media so that the material is easier to understand by elementary school children